Endothelial Cell Bioenergetics and Mitochondrial DNA Damage Differ in Humans Having African or West Eurasian Maternal Ancestry. (February 2016) - Krzywanski, David M.; Moellering, Douglas R.; Westbrook, David G.; Dunham-Snary, Kimberly J.; Brown, Jamelle; Bray, Alexander W.; Feeley, Kyle P.; Sammy, Melissa J.; Smith, Matthew R.; Schurr, Theodore G.; Vita, Joseph A.; Ambalavanan, Namasivayam; et al.
Abstract : Background—: We hypothesized that endothelial cells having distinct mitochondrial genetic backgrounds would show variation in mitochondrial function and oxidative stress markers concordant with known differential cardiovascular disease susceptibilities. To test this hypothesis, mitochondrial bioenergetics were determined in endothelial cells from healthy individuals with African versus European maternal ancestries. Methods and Results—: Bioenergetics and mitochondrial DNA (mtDNA) damage were assessed in single-donor human umbilical vein endothelial cells belonging to mtDNA haplogroups H and L, representing West Eurasian and African maternal ancestries, respectively. Human umbilical vein endothelial cells from haplogroup L used less oxygen for ATP production and had increased levels of mtDNA damage compared with those in haplogroup H. Differences in bioenergetic capacity were also observed in that human umbilical vein endothelial cells belonging to haplogroup L had decreased maximal bioenergetic capacities compared with haplogroup H. Analysis of peripheral blood mononuclear cells from age-matched healthy controls with West Eurasian or African maternal ancestries showed that haplogroups sharing an A to G mtDNA mutation at nucleotide pair 10398 had increased mtDNA damage compared with those lacking this mutation. Further study of angiographically proven patients with coronary artery disease and age-matched healthy controls revealed that mtDNA damage was associated with vascular function and remodeling and that age of disease onset was later in individuals from haplogroups lacking the A to G mutation at nucleotide pair 10398. Conclusions—: Differences in mitochondrial bioenergetics and mtDNA damage associated with maternal ancestry may contribute to endothelial dysfunction and vascular disease.